Piperine-hydroxy acid-cyclodextrin inclusion complexes; antioxidant, antiinflammatory, and stability studies: PART II (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Piperine (PIP) is a natural ingredient possessing important biological activities. However, itspractical usefulness is limited due to its low water solubility. In our previous research article (PART A), wedemonstrated inclusion complexation of PIP with cyclodextrins (CDs) in the influence of certain hydroxy acidsresulted in tremendous improvement in physicochemical characteristics of PIP. The aim of current researchwork was to study biological properties and stability analysis of PIP and its lyophilized inclusion complexes.Materials and Methods: Initially, Job’s plot experiment was carried out to assess the type of solubility andstoichiometry of complexes. The solid inclusion complexes were obtained by lyophilization and characterizedby differential scanning calorimetry (DSC), X-ray powder diffractometry (XRPD), saturation solubility, in-vitrodissolution, in-vitro antioxidant activity, and in-vivo anti-inflammatory activity in carrageenan-induced rat pawedema model. The short-term stability studies were carried out as per the ICH guidelines. Results: Duringassessment, the complexes performed better in terms of in-vitro antioxidant and in-vivo anti-inflammatory activitiesthan the native PIP. However, PIP: Hydroxypropyl β-CD (HPβCD): Ascorbic acid (AA) ternary complexes elicitedimmediate and maximum onset of anti-inflammatory action, as compared to other test samples. In the stabilitystudies, no noteworthy changes were recorded concerning DSC, XRPD, and in-vitro dissolution studies over aperiod of 6 months except complexes with HPβCD. Conclusion: Taking everything into account, complexationof PIP with CDs, in the influence of AA, would be a successful way to improve its biological properties.